The Mauriceville plasmid of Neurospora spp. uses novel mechanisms for initiating reverse transcription in vivo. - Kennell, J C (1994)
The Mauriceville plasmid and the closely related Varkud plasmid of Neurospora spp. are retroelements that propagate in mitochondria. Replication appears to occur by a novel mechanism in which a monomer-length plasmid transcript having a 3' tRNA-like structure ending in CCA is reverse transcribed to give a full-length minus-strand cDNA beginning at or near the 3' end of the RNA. Here, we show that the plasmids are transcribed in vitro by the Neurospora mitochondrial RNA polymerase, with the major in vitro transcription start site approximately 260 bp upstream of the 5' end of the plasmid transcript. The location of the transcription start site suggests that the monomer-length transcripts are generated by transcription around the plasmid combined with a site-specific RNA cleavage after the 3'-CCA sequence. The 5' ends of minus-strand cDNAs in ribonucleoprotein particles were analyzed to obtain insight into the mechanism of initiation of reverse transcription in vivo. A major class of minus-strand cDNAs begins opposite C2 of the 3'-CCA sequence, the same site used for de novo initiation of cDNA synthesis by the plasmid reverse transcriptase in vitro. A second class of minus-strand cDNAs begins with putative primer sequences that correspond to cDNA copies of the plasmid or mitochondrial transcripts. These findings are consistent with the possibility that the plasmid reverse transcriptase initiates minus-strand cDNA synthesis in vivo both by de novo initiation and by a novel template-switching mechanism in which the 3' OH of a previously synthesized cDNA is used to prime the synthesis of a new minus-strand cDNA directly at the 3' end of the plasmid transcript.